Preparation and Characterization of Novel Montmorillonite Nanocomposites - Mansa, Rola (Université d'Ottawa / University of Ottawa, 2011)
Clay minerals have historically played a consequential role in human health. While the beginnings were rooted in geophagy, a primitive act of consuming earth, the health-related uses of clay minerals have evolved and diversified over time. As excipients in pharmaceutical formulations, clay minerals can attribute novel properties onto intercalated compounds. Intercalating oxybenzone, a UV filter, within the interlamellar space of montmorillonite is desirable in order to minimize direct contact with skin. Intercalating resveratrol, a compound known for attributing beneficial effects onto human health, may be advantageous since this compound is susceptible to cis-trans isomerisation. The strategy of using alkylammonium–modified clay was undertaken and proved successful for the intercalation of oxybenzone. The field of biopolymer/layered silicate nanocomposites is heavily researched for use in a multitude of applications. Novel montmorillonite nanocomposites were prepared with neutral guar gum and cationic guar gum, using an environmentally friendly process and are fully characterized.
Keywords: clay; chemistry; montmorillonite; guar gum; oxybenzone; resveratrol; excipient; galactomannan; alkylammonium; organoclay; biopolymer; polymer; green; nanocomposite; bionanocomposite; hybrid; pharmaceutical